Microstructure and Thermal and Tensile Properties of Poly(vinyl alcohol) Nanocomposite Films Reinforced by Polyacrylamide Grafted Cellulose Nanocrystals. Issue 4 (2nd April 2020) - Li, Bengang; Wu, Chao; Zhang, Yandan; Cao, Xuzhi; Luo, Zhenyang
Abstract: Polyacrylamide grafted cellulose nanocrystals (CNC-g-PAM) were incorporated into poly(vinyl alcohol) (PVA) by a solution casting method to fabricate nanocomposite films with enhanced thermal and tensile properties. The microstructure and the thermal and tensile properties of the PVA/CNC-g-PAM nanocomposite films were investigated as a function of CNC-g-PAM content. Infrared spectroscopy corroborated the presence of hydrogen bonds between PVA and the PAM on the surface of the CNC. Polarized optical microscopy and scanning electron microscopy revealed good dispersion of the CNC-g-PAM in the PVA matrix and good interfacial compatibility. Accordingly, the initial degradation temperature of the nanocomposite films was elevated slightly compared to pristine PVA film. The glass transition temperature, melting temperature, and crystallinity of the PVA also varied slightly after the incorporation of the CNC-g-PAM. At both 0% and 50% RH, the nanocomposite films showed an obvious increase of elastic modulus, no apparent change of breaking strength and a drastic reduction of elongation at break with increasing CNC-g-PAM content.